2019
DOI: 10.3390/en12214106
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Unsteady Aerodynamic Performance of Novel Adaptive Airfoil for Vertical Axis Wind Turbine

Abstract: The aerodynamic performance of the blade determines the power and load characteristics of a wind turbine. In this paper, numerical research of the active deformation of an airfoil with equal thickness camber line was carried out, which shows the great potential of this active flow control method to improve the flow field. The NACA0012 is taken as the reference airfoil, and the inflow wind speed is 9 m/s, the chord length of the airfoil is 0.4 m, and the Reynolds number is 2.5 × 105. The influence factors, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In the simulations, because the Reynolds number is greater than the critical Reynolds number under subsonic and supersonic conditions, a turbulence model is introduced to consider the effect of turbulence on the calculated results (Tong et al 2019).…”
Section: Turbulent Airflow Modelmentioning
confidence: 99%
“…In the simulations, because the Reynolds number is greater than the critical Reynolds number under subsonic and supersonic conditions, a turbulence model is introduced to consider the effect of turbulence on the calculated results (Tong et al 2019).…”
Section: Turbulent Airflow Modelmentioning
confidence: 99%
“…The SST k-ω turbulence model is a two-equation eddy viscosity turbulence model, which is based on the baseline k-ω mode and considers the transport of the turbulence shear stress in the definition of the turbulent viscosity [20]. The Wilcox k-ω turbulence model is utilized in the inner region of the boundary layer and the standard k-ε model is utilized in free shear flows and the outer area [21]. The transport equation for the turbulent kinetic energy k is: The transport equation for the specific consumption rate ω is:…”
Section: Geometrical Parameters Of the Turbine And Cfd Simulation Str...mentioning
confidence: 99%
“…Blades that undergo adaptive changes in surface shape according to the above rules will have a higher capacity in absorbing wind energy, and effectively improve the wind energy extraction efficiency for this type of VAWT. Based on Ying's research, Tong et al [17] designed and made a blade model suitable for VAWT whose leading edge and trailing edge can have active changes simultaneously with the single input motivation. Firstly, based on the continuous deflection and deformation method of the leading and trailing edges of the airfoil with constant thickness (according to the wing rib concept and NACA0012 airfoil as an example), the blade deformation with different curvatures were achieved by applying a pre-tightening force.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the comparison revealed that the aerodynamic performance characteristics of the blade under different deformation factors, and the results could provide reference for subsequent unsteady experiments. Tong et al [17] have also conducted numerical simulation concerning the influence of the active deformation movement of the uniform-thickness mid-curve on the aerodynamic performance of the airfoil with NACA0012 as the reference airfoil at different angles of attack before and after the stall. Under the condition that the maximum deformation position of the airfoil was at 0.4 c, the incoming wind speed was of 9 m/s, the airfoil chord length was of 0.4 m, and the Reynolds number was of 2.5 × 10 5 .…”
Section: Introductionmentioning
confidence: 99%